Response of two broccoli varieties to different sowing dates (International Journal of Environmental Sciences, 2025)
An experiment was carried out in the vegetable field managed by the Department of Horticulture and Landscape Design, located within the College of Agriculture and Forestry at the University of Mosul, during the fall growing season of 2024 to study the physiological effects of three broccoli sowing dates (10 August, 20 August, and 1 September) using two hybrid varieties of broccoli plants: Matsuri Japanese hybrid, Lotus Dutch hybrid, thus the experiment included 6 factorial treatments (2*3) implemented in the field using a factorial experiment in a complete randomized block design RCBD with three replicates. The results of the statistical analysis using the SAS electronic program and at a probability level of 5% according to Duncan's multiple range test showed the following: sowing broccoli on the first date is preferred in order to increase productivity traits, and the Lotus variety significantly outperformed the Matsuri variety in productivity traits. Cultivating the Lotus hybrid during the first sowing date (10 August) resulted in marked improvements across all productivity-related traits.The interaction effect between sowing date and cultivars showed a significant individual effect for each factor and each trait.